Research progress of CRISPR-based biosensors and bioassays for molecular diagnosis - Chen, Kun; Shen, Ziyi; Wang, Guanzhen; Gu, Wei; Zhao, Shengchao; Lin, Zihan; Liu, Wei; Cai, Yi; Mushtaq, Gohar; Jia, Jia; Wan, Chunpeng (Craig); Yan, Tingdong (Frontiers in Bioengineering and Biotechnology, 2022)
CRISPR/Cas technology originated from the immune mechanism of archaea and bacteria and was awarded the Nobel Prize in Chemistry in 2020 for its success in gene editing. Molecular diagnostics is highly valued globally for its development as a new generation of diagnostic technology. An increasing number of studies have shown that CRISPR/Cas technology can be integrated with biosensors and bioassays for molecular diagnostics. CRISPR-based detection has attracted much attention as highly specific and sensitive sensors with easily programmable and device-independent capabilities. The nucleic acid-based detection approach is one of the most sensitive and specific diagnostic methods. With further research, it holds promise for detecting other biomarkers such as small molecules and proteins. Therefore, it is worthwhile to explore the prospects of CRISPR technology in biosensing and summarize its application strategies in molecular diagnostics. This review provides a synopsis of CRISPR biosensing strategies and recent advances from nucleic acids to other non-nucleic small molecules or analytes such as proteins and presents the challenges and perspectives of CRISPR biosensors and bioassays.